Integrating Social Capital and Finansial Capital for Beef Cattle Farmers Economic Solutions in Kediri Regency, East Java Province, Indonesia - Linawati Linawati; Nur Solikin (Journal of Development Research, 2020)
The culture of mutual cooperation with rural communities is one of the social capital that is still ongoing, especially in running livestock businesses. This study aims to analyze the social capital and financial capital of beef cattle breeders. The research location was chosen in conjunction in Semen District, Kediri Regency. Interviewing and filling out questionnaires are instruments in this descriptive study. The results showed that the social capital of cattle breeders in the medium category, financial capital came from a joint venture (gaduhan system). The conclusion is that the existence of social and financial capital due to the gaduhan system is a solution to economic problems in rural areas. An increase in social capital may have an impact on increasing financial capital.